Acoustic fields of acid suspensions containing cassava bagasse: Influence of physical properties on acoustic attenuation. (June 2021) - Polachini, Tiago Carregari; Mulet, Antonio; Telis-Romero, Javier; Cárcel, Juan A.
Abstract: The effects produced by high-intensity ultrasound application during the acid pretreatment of biomass can enhance its later conversion into bioethanol. Therefore, it is interesting to evaluate how residues, such as cassava bagasse (CB), affect the actual acoustic field applied and, thus, the magnitude of its effects. For this, calorimetric method was used to estimate acoustic energy and the efficiency of electric-acoustic energy conversion in acid suspensions containing different CB concentrations (2–10%). Tests were carried out under different input powers, from 160 to 400 W (24 kHz), at different distances (1.5–5.5 cm) from the sonotrode. Thus, the experimental acoustic intensity measured varied from 12.90 to 68.57 W·cm −2, the highest values being registered in the suspensions with the lowest CB content (65.55–36.81% of conversion yield close to the sonotrode). Attenuation was also addressed during sound wave propagation, finding a constant value of 0.021 cm −1 . Polynomial models were well fitted to acoustic parameters and acoustic intensity exhibited a high correlation ( r >0.87 and p value ≤ 0.05) with the experimental thermophysical properties of the suspensions.